Parcelamento de fontes alternativas de nitrogênio no milho safrinha em sucessão à soja - Soratto, Rogério Peres [UNESP]; Costa, Tiago Aparecido Mingotti da; Fernandes, Adalton Mazetti [UNESP]; Pereira, Magno; Maruyama, Wilson Itamar (My University, 2012)
Increasing out-of-season corn productivity is possible by the application of nitrogen fertilizers even when in succession to soybean. On the other hand, information concerning the best sources of nitrogen and ways of splitting the doses to be applied is still scarce. Having that in mind, an experiment was carried out viewing to evaluate the effects of sources of nitrogen and ways of splitting doses of those N fertilizers on out-of-season corn sown in succession to soybean cultivated in a no-tillage system. The experiment took place in Chapadão do Céu, state of Goiás, Brasil (latitude of 18°35’42’’ South, longitude of 52°47’59’’ West and mean altitude above sea level of 802 m) in an Acrutox. The experimental units were distributed in the field in accordance with a randomized complete block design, in a factorial scheme 3 X 5 + 1, with four replications. Three were the sources of N: urea, urea extruded with starch (Amireia®) and ammonium sulfonitrate with a nitrification inhibitor (Entec®) and five the ways of splitting the nitrogen dose : 90-0, 60-30, 45-45, 30-60, and 0-90 in which the first fraction was applied at sowing and the second in side dressing. In addition to those, there was a check treatment, without N. All plots received, at sowing, 12 kg ha-1 of N by the mixture NPK. The ways of splitting the N dose and the sources of N had no significant effect on the levels of N and S in the leaves, first ear height, the final plant population, the number of ears per plant, and the number of grains per ear. N in the Entec® form at the highest doses applied in side dressing resulted in the highest grain yield, independently of the way the N dose was split. Only in the form Entec® the dose of 90 kg ha-1 of N increased grain productivity by 9.6% in comparison with the check treatment.

Incrementos de produtividade da cultura do milho safrinha podem ser obtidos com a aplicação de nitrogênio, mesmo quando cultivado em sucessão à soja. Porém, existe necessidade de esclarecimentos quanto à melhor fonte nitrogenada e à forma de parcelamento para essa modalidade de cultivo. Com o objetivo de avaliar a influência de fontes e formas de parcelamento do N no milho safrinha, cultivado após soja no sistema plantio direto, conduziu-se o experimento em um Latossolo Vermelho distrófico, em Chapadão do Céu (GO). O delineamento experimental foi o em blocos casualizados, num esquema fatorial 3x5+1, com quatro repetições. Foram estudadas três fontes (ureia, ureia extrusada com produtos amiláceos (Amireia® 180S) e sulfonitrato de amônio com inibidor de nitrifica- ção (Entec® 26)), cinco formas de parcelamento (90-0; 60-30; 45-45; 30-60 e 0-90 kg ha-1 , aplicados, respectivamente, de forma complementar na semeadura e em cobertura) e uma testemunha (sem N complementar). Todos os tratamentos receberam 12 kg ha-1 de N mediante a formulação NPK aplicada na semeadura. As fontes e as formas de parcelamento não influenciaram o teor de N e S foliar, a altura de inserção da primeira espiga, a população final de plantas, o número de espigas por planta e o número de grãos por espiga. A aplicação de N, na forma de Entec® , em maiores doses em cobertura, proporcionou maior massa dos grãos. Independentemente do parcelamento, a aplicação de 90 kg ha-1 de N, apenas na forma de Entec® , aumentou a produtividade de grãos em 9,6%, em rela- ção à testemunha.
Effects of splitting doses of nitrogen fertilizers from alternative sources on out-of-season corn following soybean
Keywords: Nitrogen effect; Application time; No-tillage; Zea mays; Efeito do nitrogênio; Época de aplicação; Plantio direto